Analysis of E-Waste Recycling Intention in Ho Chi Minh City, Vietnam - Thao Le Thi Kim; Han Bui Thi Ngoc; Trang Nguyen Ha (Journal of Technical Education Science, 2024)
Due to the increased demand for electrical and electronic devices, Vietnam has emerged as one of the major importers of electronic goods in Southeast Asia. This corresponds to Vietnam facing an escalating issue of electronic waste. In light of this concern, the purpose of this study was to investigate the individual intention regarding the recycling of electronic waste. To achieve this objective, a survey was conducted among 1020 respondents with varying genders, and educational levels in Ho Chi Minh City. The collected data was analyzed sing SPSS and AMOS software, enabling the development of a structural model. The findings of the study found that social pressure was the most influential factor affecting the intention to recycle electronic waste. Following closely behind were inconveniences, economic factors, attitudes, and awareness. Based on the outcome, it is recommended that policymakers should focus on creating effective advocacy programs, enhancing convenience, and improving public understanding and awareness in order to help reduce electronic waste.